Collaborative Ways of Knowing: Storytelling, Metaphor and the Emergence of the Collaborative Self - Randee Lipson Lawrence; Craig A. Mealman (Adult Education Research Conference, 1999)
This study explores collaborative inquiry as a research methodology through an examination of the processes employed by the co-researchers. The paper describes metaphor and storytelling, two heuristics that assisted in the collection and analysis of data and discusses the role of the collaborative relationship in the construction of knowledge.